ALIH FUNGSI TROTOAR UNTUK PEJALAN KAKI - Sonya Sidjabat (Institut Transportasi dan Logistik Trisakti, 2016)
In Jakarta, the sidewalks for pedestrians, are not only bad but also switched functionally. With that being said, sidewalks and zebra cross have become meaningless. PELANGI, one of the Non-Governmental Organization (LSM) that works dominately on the urban studies, mentioned that 65% of the accident on main roads, sadly involved the death of pedestrians, whereas 35% of the victims are underaged kids. These facts, though, have to be considered as our motivation to work on the sidewalks, making it suitable and comfortable to be walked through (walkable). Being supported and encouraged by the qualitative method and literature, indeed, pedestrians also have the same rights in using the roads.